"As good as your word": face-threat mitigation and the use of instructor nonverbal cues on students' perceptions of digital feedback. Issue 2 (3rd April 2018) - Clark-Gordon, Cathlin V.; Bowman, Nicholas D.; Watts, Evan R.; Banks, Jaime; Knight, Jennifer M.
ABSTRACT: Research has established that students often consider the delivery of instructor feedback to be a face-threatening event. To minimize the potential negative effects of feedback, verbal and nonverbal face-threat mitigation (FTM) strategies are utilized by instructors. Advances in digital feedback systems, like online documents and learning management platforms, allow instructors to add nonverbal elements, such as profile pictures or emojis, to this feedback. Two mixed-method studies were employed to investigate the role of these nonverbal cues in digital feedback. Study 1 ( N  = 236) employed a 2 by 2 experiment (presence or absence of FTM tactics by presence or absence of instructor picture), showing that FTM strategies have substantial positive impact on feedback and instructor perceptions, and that the inclusion of instructor pictures with this feedback has no effect. Study 2 ( N  = 218) utilized a 2 by 2 experimental design (presence or absence of FTM tactics by presence or absence of matched-valence emojis). Results confirm main effects of FTM techniques (mitigation strategies lead to positive effects), but the addition of emojis had no perceptible influence. Implications for technology-driven instructional feedback are discussed.